Effects of nano thickener deposited film on the behaviour of starvation and replenishment of lubricating greases - Lu Huang; Dan Guo; Xiang Liu; Guoxin Xie; George T. Y. Wan; Shizhu Wen (Friction)
Abstract The mechanism of grease replenishment in and around a starved point contact was studied in this work. Greases made of different thickeners and same base oil were tested and compared. Disappearing and re-formation of a dynamic grease reservoir during operation revealed that grease bled oil to replenish contact. However, the replenishment process was slow because of the presence of grease fingers along the track and thickener-deposited film inside the track. The contact angles of base oil on the chromium-coated surface and thickener-deposited surfaces were measured. Results proved that the contact angle on the deposited film remarkably increased compared with that on the chromium-coated surface from 25° to more than 40°. However, the deposited film could be consumed with continuous rolling, and replenishment was then enhanced.